RECOMMENDATIONS FOR COVID-19 PREVENTION AND TESTING FOR HEMATOPOIETIC CELL TRANSPLANT CENTERS IN BRAZIL : September 2023 - Mendes, Ana Verena de Almeida; Carlesse, Fabianne; Ramos, Jessica; Garnica Maiolin, Márcia; Machado, Clarisse Martins (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2023)
From February 2020 to May 2023, 37,625,916 cases of COVID-19 were recorded in Brazil, which led to 2,173,359 hospitalizations due to severe acute respiratory syndrome (SARS) with 703,291 deaths due to COVID-19. More than 14 million cases were registered in 2021 and 2022. However, there was a significant drop in the number of hospitalizations for SARS and the COVID-19 fatality rate in 2022, which certainly reflects the impact of mass vaccination in the country, started in February 2021.